Effectiveness of an Education Program ConcerningCardiotocography on Nurses- MidwivesPractice in Maternity Hospitals at Baghdad City. - Oleiwi, Sajidah; abbas, Iqbal (Iraqi National Journal of Nursing Specialties, 2018)
Objectives: To identify the effectiveness program on nurse- midwife practice concerning performed cardiotocography to pregnant women and to find out the relationship between nurse- midwife practice and certain studied variables. Methodology: A quasi-experimental design (pretest-post test approach) was conducted at three sector AlRussafa directorate, AL- Karckh directorate and Medical City Directorate from the period of March, 26th 2014 to August, 30th 2015. A non-probability sample consisted of (130) nurse -midwives were selected and divided into two groups (65) nurses-midwives (case group) who exposed to the educational program and (65 ) nursesmidwives who didn’t expose to the program considered as control group . Data were collected through the use of questionnaire and checklist concerning practice for cardiotocography Result: in general the results show a statistical significant improvement of nurses-midwives practices concerning cardiotocograhy. Recommendation: The study was recommended that print and distribute guide booklets and improve their practice and provide an opportunity for nurses-midwives to be enrolled training sessions concerning cardiotocography